Variability in gut microbiota response to an inulin-type fructan prebiotic within an in vitro three-stage continuous colonic model system. (July 2017) - Healey, G.; Murphy, R.; Butts, C.; Brough, L.; Rosendale, D.; Blatchford, P.; Stoklosinski, H.; Coad, J.
Abstract: Gut microbiota have a major influence on human health and disease. Dietary interventions have been shown to beneficially modulate the gut microbiota and improve health; however, it appears there is large inter-individual variability in gut microbiota responsiveness to dietary interventions. We aimed to determine whether different fermentable carbohydrate content media, mimicking Western and Prudent style dietary patterns, influence gut microbiota response to an inulin-type fructan prebiotic using an in vitro three-stage continuous colonic model system. We demonstrated that the addition of an inulin-type fructan prebiotic led to shifts in the organic acid concentrations and bacterial taxa in both the low (LF) and high fermentable carbohydrate medium (HF) gut models. The shifts that occurred after the addition of the prebiotic significantly differed between the LF and HF gut models. Acetate increased in the HF gut models but decreased in the LF gut models (p=0.021). The increases that occurred in Firmicutes (p=0.026), Lactobacillus (p=0.045) and Mitsuokella (p=0.012) were significantly greater in the HF gut models. Megasphaera (p=0.033) and an unknown genus of Enterobacteriaceae (p=0.011) decreased in the LF gut models but increased in the HF gut models. The reduction in an unknown genus of Lachnospiraceae (other) was significantly greater in LF gut models (p=0.040). Additionally, large inter- and intra-donor variability in gut microbiota responsiveness to the prebiotic were demonstrated. This study demonstrates that media with different fermentable carbohydrate contents caused variability in gut microbiota responsiveness to an inulin-type fructan prebiotic; however, these results will need to be replicated in an i n vivo study.